A Prospective Evaluation of the Acute Effects of High Altitude on Cognitive and Physiological Functions in Lowlanders - Falla, Marika; Papagno, Costanza; Dal Cappello, Tomas; Vögele, Anna; Hüfner, Katharina; Kim, Jenny; Weiss, Elisabeth M.; Weber, Bernhard; Palma, Martin; Mrakic-Sposta, Simona; Brugger, Hermann; Strapazzon, Giacomo (Frontiers in Physiology, 2021)
Cognitive function impairment due to high altitude exposure has been reported with some contradictory results regarding the possible selective cognitive domain involvement. We prospectively evaluated in 36 lowlanders, exposed for 3 consecutive days to an altitude of 3,269 m, specific cognitive abilities (attention, processing speed, and decision-making) required to safely explore the mountains, as well as to work at altitude. We simultaneously monitored the physiological parameters. Our study provides evidence of a reduced processing speed in lowlanders when exposed to altitude in the first 24 h. There was a fairly quick recovery since this impairment was no more detectable after 36 h of exposure. There were no clinically relevant effects on decision-making, while psychomotor vigilance was unaffected at altitude except for individuals with poor sleep. Significant changes were seen in physiological parameters (increased heart rate and reduced peripheral oxygen saturation). Our results may have practical implications, suggesting that individuals should practice prudence with higher ascent when performing risky activities in the first 24–36 h, even at altitudes below 3,500 m, due to an impairment of the cognitive performance that could worsen and lead to accidents.